PENGARUH PENERAPAN MODEL PEMBELAJARAN dISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGERI 16/24 BULU TELLUE KAB. PANGKEP. - Yuni, Asri; Sulfasyah; Haslinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by students' low critical thinking skills in Indonesian language learning, particularly in reading comprehension. Students still experience difficulty identifying main characters, explaining character traits, providing evidence from the text, and drawing logical conclusions. This study aims to determine students' critical thinking skills before and after the implementation of the Discovery Learning model and to determine the model's effect on the critical thinking skills of fourth-grade students at SD Negeri 16/24 Bulu Tellue, Pangkep Regency. This study used a quantitative approach with a pre-experimental design and a One Group Pretest-Posttest Design. Twelve fourth-grade students of SD Negeri 16/24 Bulu Tellue, Pangkep Regency participated in the study. Data were collected through tests, observation, and documentation. Data were analyzed using descriptive and inferential statistics with a paired sample t-test. The results showed an average pretest score of 42.50 and a posttest score of 75.00. This improvement indicates that students' critical thinking skills improved after the implementation of the Discovery Learning model. Students are better able to analyze the content of the reading, provide logical reasons, and draw appropriate conclusions. The results of the hypothesis test show a significance value of 0.000 < 0.05 so that H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the application of the Discovery Learning learning model has a significant effect on critical thinking skills in reading comprehension of fourth-grade students of SD Negeri 16/24 Bulu Tellue, Pangkep Regency.